P316 Structure-based drug design for neisseria gonorrhoeae, chlamydia trachomatis, and mycoplasma genitalium. (14th July 2019) - Barrett, Kayleigh; Michaels, Samantha; Navaluna, Edelmar; Siddaramaiah, Latha; Wood, Gwendolyn; Phan, Isabelle; Zhang, Zhongsheng; Staker, Bart; Subramanian, Sandhya; Totten, Patricia; Soge, Olusegun; Myler, Peter; et al.
Abstract : Background: The UW-STI consortium seeks to develop novel antimicrobials for the treatment of syndromically similar infections caused by Neisseria gonorrhoeae (GC), Chlamydia trachomatis (CT), and Mycoplasma genitalium (MG). Methods: We utilize a structure-based validation pipeline embedded with a gated series of criteria for progressing druggable enzyme targets, and for identifying and advancing compounds active against these protein targets. The pipeline includes orthologous and essential enzyme target identification, structure determination, compound library screening, antimicrobial susceptibility testing, hit optimization, and chemical-genetic target validation. Results: To date, we have identified over 80 enzyme candidates that are essential, single copy genes in both GC and MG; 7 GC structures, 1 CT structure and 1 MG structure have been solved by crystallography, and soluble expression has been achieved for 19 GC, 20 CT, and 3 MG recombinant enzymes. Several structures common to two bacteria have been solved including tryptophan-tRNA synthetase, lysyl-tRNA synthetase, and ribose-5-phosphate isomerase A/B. Phenylalanyl-tRNA synthetase (PheRS) is among our highest priority targets and is presented as a proof of concept for multi-organism drug development. PheRS is a validated drug target with divergence from its human counterpart, as modeled by the group. In lieu of crystal structures, the GC PheRS alpha and beta complex was modeled using the Rosetta software suite. Multiple cloning and expression strategies have been employed including surface mutations, solubility tags, engineered truncations, and co-expression of both subunits, in hopes of producing crystals. A PheRS001 inhibitor was synthesized from published literature and proved active against GC PheRS with an IC50 of 93 nM, and in antimicrobial testing against all three bacteria: 120 µg/ml (CT MIC) and 18 µg/ml (MG and GC MIC). Conclusion: PheRS is a promising example of our pipeline capabilities in our three-pronged approach to produce 5–10 therapeutic leads and aid in the global fight against antibiotic resistance in sexually-transmitted bacterial infections. Disclosure: No significant relationships.